Commonalities between US and Hungarian Universities with regards to Organizational Development and Controls against the Moral Hazards of Administration - Schmidt, Christopher R.; Király, Ágnes (Marketing & Menedzsment, 2019)
AIMS OF THE PAPER This paper explores key control elements inside of Hungarian and American Universities that guide organizational development via the strategic planning processes and looks for evidence of mechanisms that would prevent, identify, and allow the remediation of breaches of fiduciary duty related to the moral hazards of administration The aim of this paper is to establish criteria for comparison and evaluation, centering on the use of internet communication technology to provide transparency and effective governance. METHODOLOGY Within the frames of qualitative research, we analyzed the strategic plans of 6 American and 6 Hungarian universities and looked at institutional structures for organizational development and learning that would improve the institutions’ ability to detect theft and corruption on its own. The study explores key control points to verify (1) the existence and availability of the strategic plan, (2) whistleblowing as a defined process for the solicitation of concerns, (3) internal controls as a strategic objective, (4) the existence and availability of code of ethics, (5) public solicitation of actual complaints received, (6) public report of findings; whether (7) organizational learning was a defined goal, and (8) public reporting of achievements. MOST IMPORTANT RESULTS No institutions evaluated met all of our criteria. Overall the Hungarian institutions had a slightly higher average fulfillment of the criteria at 61% compared to the US fulfillment of rate of 56%. The fact that specific criteria had extremely low fulfillment rates, indicates that internal controls as institutional priorities and public presentation of these processes for the purpose of enhancing efficacy of governance and organizational learning is inconsistently pursued within public university administrations. RECOMMENDATIONS Universities in the USA should focus more on internal control and the follow-up of their strategic achievements. Hungarian universities need to elaborate the whistleblowing process and should share more information about the solicitation process and the findings with the public.